Associations with food allergy‐related psychological distress in a global sample of adults, children and caregivers - S. E. M. Purser; C. J. Jones; J. L. P. Protudjer; L. J. Herbert; C. Screti; C. Roleston; E. Mattacola; H. A. Brough; C. Warren; L. Polloni; A. F. Santos; R. Gupta; et al. (Clinical and Translational Allergy, 2025)
Abstract Objective Food allergy (FA) impacts health‐related quality of life and mental health. Understanding what variables are associated with psychological distress can help healthcare providers direct patients to appropriate support. As part of the study, Global Access to Psychological Services (GAPS) for FA and associations with FA‐related psychological distress were explored in adults with FA and caregivers of children with FA. Methods Participants completed online surveys in seven languages. Participants reported the types of FA‐related distress they or their child experienced, along with demographic and FA‐related information. Associations with distress were analysed using regression models. Results N = 1329 adults with FA and N = 1373 caregivers of children with FA from 27 countries participated. Of the 21 different types of distress selected, anxiety about an allergic reaction was the most common (62.5% adults; 72.6% caregivers). Females reported significantly more types of distress than males (p < 0.001). There were significant differences between countries (all p < 0.05‐0.001); participants in Australia, Brazil, Canada, and the United Kingdom consistently reported more types of distress than European countries or the United States. In regression models, country of residence, number of FAs, and symptoms were significantly associated with distress. Additional associations included adrenaline autoinjector (AAI) prescription, being female, anaphylaxis and comorbidities in adults; in caregivers having a younger child, longer time elapsed since FA diagnosis, being female, AAI prescription and anaphylaxis; and in children being older and living longer with FA. Conclusions FA‐related distress is experienced differently across countries. Understanding associations with types of distress can help direct healthcare services and psychological support to where it is needed most.